2019
DOI: 10.11604/pamj.2019.32.141.17166
|View full text |Cite
|
Sign up to set email alerts
|

On artherogenic index of plasma in sickle cell anaemia patients

Abstract: Introduction Sickle cell anaemia (SCA) is an inherited abnormality of haemoglobin associated with reduced life expectancy. Patients' complications include dyslipideamia. This study was aimed at determining the artherogenic index of plasma (AIP) in sickle cell anaemia patients and compares the value to HbAA controls value. A high AIP is strongly predictive of elevated cardiovascular risk. Methods A comparative study was conducted among SCA patients attending the haematol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Dyslipidemia has been considered one of the subphenotypes of SCD, with hypocholesterolemia being a common characteristic in this population, differently than individuals without SCD ( 7 , 23 , 27 , 28 ). The mechanism for this change is not clear, but inflammation, oxidative stress, and chronic hemolysis have been indicated as involved factors ( 4 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyslipidemia has been considered one of the subphenotypes of SCD, with hypocholesterolemia being a common characteristic in this population, differently than individuals without SCD ( 7 , 23 , 27 , 28 ). The mechanism for this change is not clear, but inflammation, oxidative stress, and chronic hemolysis have been indicated as involved factors ( 4 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The observation of the lowest Hb levels and the highest nitric oxide metabolites in individuals with sickle cell anemia (SCA) with low HDL-C levels (HDL-C <40 mg/dL) ( 6 ) suggests that hypocholesterolemia may be related to pathophysiological factors of the disease itself, such as high erythropoietic activity because of the increased demand for cholesterol ( 7 ). Hemolysis, oxidative stress, and inflammation in SCD cause reduction in HDL-C and Apo A1 levels, and it has been suggested that this is due to dysfunction and slowed functioning of the reverse cholesterol transport ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The higher the HDR, the more risk. AIP< 0.11 low risk, 0.11-0.21 moderate or intermediate risk, >0.21 increased risk for humans[21]…”
mentioning
confidence: 99%